Bee products prevent agrichemical-induced oxidative damage in fish. - Daiane Ferreira (Public Library of Science (PLoS), 2013)
In southern South America and other parts of the world, aquaculture is an activity that complements agriculture. Small amounts of agrichemicals can reach aquaculture ponds, which results in numerous problems caused by oxidative stress in non-target organisms. Substances that can prevent or reverse agrichemical-induced oxidative damage may be used to combat these effects. This study includes four experiments. In each experiment, 96 mixed-sex, 6-month-old Rhamdia quelen (118±15 g) were distributed into eight experimental groups: a control group that was not exposed to contaminated water, three groups that were exposed to various concentrations of bee products, three groups that were exposed to various concentrations of bee products plus tebuconazole (TEB; Folicur 200 CE™) and a group that was exposed to 0.88 mg L(-1) of TEB alone (corresponding to 16.6% of the 96-h LC50). We show that waterborne bee products, including royal jelly (RJ), honey (H), bee pollen (BP) and propolis (P), reversed the oxidative damage caused by exposure to TEB. These effects were likely caused by the high polyphenol contents of these bee-derived compounds. The most likely mechanism of action for the protective effects of bee products against tissue oxidation and the resultant damage is that the enzymatic activities of superoxide dismutase (SOD), catalase (CAT) and glutathione-S-transferase (GST) are increased.